2022
DOI: 10.1186/s10194-022-01433-9
|View full text |Cite
|
Sign up to set email alerts
|

Real-world long-term efficacy and safety of erenumab in adults with chronic migraine: a 52-week, single-center, prospective, observational study

Abstract: Background Clinical trials have shown that erenumab is effective and well-tolerated for the preventive treatment of chronic migraine. To extend the results from clinical trials, we assessed the real-world efficacy and safety of erenumab in patients with chronic migraine from the outpatient clinic at the Danish Headache Center. Methods A 52-week, single-center, prospective, observation study of erenumab in adults with chronic migraine who are eligib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 23 publications
6
42
0
Order By: Relevance
“…Real-world data with the use of CGRP(-R) mAbs in clinical practice show similar findings. About half of CM patients have a 50% reduction of MMD after three months of treatment [ 15 , 16 ]. At the same time, up to one-third of patients do not respond to mAbs treatment, while 20% have a very high benefit with a reduction of ≥ 75% in MMD along a tremendous improvement of quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Real-world data with the use of CGRP(-R) mAbs in clinical practice show similar findings. About half of CM patients have a 50% reduction of MMD after three months of treatment [ 15 , 16 ]. At the same time, up to one-third of patients do not respond to mAbs treatment, while 20% have a very high benefit with a reduction of ≥ 75% in MMD along a tremendous improvement of quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Also, post‐marketing clinical studies or reports did not reveal a significant rate of effluvium or alopecia in patients using monoclonal CGRP antibodies 1 . To the best of our knowledge, we also did not find a case report on effluvium associated with the use of monoclonal CGRP antibodies in medical databanks but alopecia was reported in real‐world studies on monoclonal CGRP antibodies 2 . However, when we started treating patients with migraine at the end of 2018 with monoclonal CGRP antibodies in our supraregional tertiary headache clinic, we observed a few patients reporting hair loss after onset of treatment.…”
Section: Patient (Sex Age) Monoclonal Antibody (In Order Of Use) Effl...mentioning
confidence: 65%
“…To date, no real-world studies of eptinezumab and gepants have been published. Real-world studies (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) assessed the efficacy of erenumab using the following parameters: mean reduction in monthly headache days (MHDs), monthly migraine days (MMDs), monthly acute medication days (AMDs) and the proportion of patients reporting a !50% reduction in MMD in patients with EM and CM (Table 2). The treatment duration ranged from two to 12 months, with a commercially available dose (i.e., erenumab 70 or 140 mg every four weeks).…”
Section: Real-world Studiesmentioning
confidence: 99%
“…Treatment interruption due to lack of effectiveness and adverse events was 0%–22% and 0%–12%, respectively. Real-world studies of erenumab reported that 22%–83% of patients converted from CM to EM (16,17,19,27,30), and one subgroup analysis showed a higher rate of conversion among patients with difficult-to-treat migraine with a long history of CM and multiple prior unsuccessful prophylactic treatments, including BTA (31).…”
Section: Efficacy and Safety Of New Therapies In Patients Who Failed ...mentioning
confidence: 99%